Dynamic Operation of a Heat Exchanger in a Thermally Integrated Photovoltaic Electrolyzer. Issue 2 (25th December 2022) - Kemppainen, Erno; Bagacki, Rory; Schary, Christian; Bao, Fuxi; Dorbandt, Iris; Janke, Stefan; Emery, Quiterie; Stannowski, Bernd; Schlatmann, Rutger; Calnan, Sonya
Abstract : The outdoor operation of an up‐scaled thermally photovoltaic electrolyzer (PV EC), constructed using a heat exchanger (HE) made of low‐cost materials, compared to its nonintegrated counterpart to quantify heat transfer and its effects, is studied. Thermal coupling of the PV and EC can reduce the difference between their temperatures, benefitting device performance. Such devices can produce hydrogen at rooftop installations of small‐to‐medium‐sized nonindustrial buildings. The devices are tested outdoors using automated real‐time monitoring. Under ≈880 W m −2 peak irradiance, they produced hydrogen at ≈120 and ≈110 mL min −1 rate with and without HE, respectively, corresponding to about 8.5% and 7.8% solar‐to‐hydrogen efficiencies. During about 700 h of testing, the HE is beneficial at over ≈500 W m −2 due to cyclic device operation. Under lower irradiance levels, pumping previously heated electrolyte through the HE increases the PV and reduces the electrolyte temperature, reducing the device performance. The HE increases the cumulative hydrogen production (≈800 L from both devices), so even relatively modest heat transfer rates can improve the PV EC operation. Improving the HE should further increase the benefits, but additional measures may be needed to maximize the hydrogen production. Abstract : In sunny conditions, thermal integration of a photovoltaic (PV) module and an electrolyzer (EC) stack improves device performance by cooling the PV and warming the ECs. However, in the evening and in the morning, the PV may be warmed, the electrolyte cooled, and the efficiency reduced. This can complicate device optimization and some temperature control measures may be needed.